Optimization and Chemical Characterization of Biosurfactant Produced from a Novel Pseudomonas guguanensis Strain Iraqi ZG.K.M - Ghazi Faisal, Zeena; Sallal Mahdi, Mayaada; Alobaidi, Khalid H. (International Journal of Microbiology, 2023)
Microbial surfactants are widely used in medical, pharmaceutical, agricultural, industrial, food, and cosmetics applications. In the present study, 85 indigenous bacteria were isolated from petroleum-contaminated soils of the Al Dourah refinery, electric power station, and electric generators in Baghdad, Iraq. Twenty nine isolates gave positive results in both blood agar and blue agar medium and were secondarily screened. One isolate was selected as a potent biosurfactant producer and molecularly identified and recorded in the NCBI GenBank nucleotide sequence database as Pseudomonas guguanensis strain Iraqi ZG.K.M. In optimized conditions, this strain can produce about 3.01 g/l of biosurfactant. The product could reduce the surface tension from 72 to 38 ± 0.33 mN/m and have E24% of 52 ± 0.33%. This biosurfactant was preliminarily specified to be a glycolipid and characterized as a rhamnolipid with anionic nature, usually to be a monorhamnolipid as evident from TLC, FTIR, and GC-MS analyses.